Enhanced control of Mycobacterium Tuberculosis Extrapulmonary Dissemination in Mice by an Arabinomannan-protein Conjugate Vaccine (2017)
ABSTRACT: Currently there are a dozen or so of new vaccine candidates in clinical trials for prevention of tuberculosis (TB) and each formulation attempts to elicit protection by enhancement of cellmediated immunity (CMI). In contrast, most approved vaccines against other bacterial pathogens are believed to mediate protection by eliciting antibody responses. However, it has been difficult to apply this formula to TB because of the difficulty in reliably eliciting protective antibodies. Here, we developed capsular polysaccharide conjugates by linking mycobacterial capsular arabinomannan (AM) to either Mtb Ag85b or B. anthracis protective antigen (PA). Further, we studied their immunogenicity by ELISA and AM glycan microarrays and protection efficacy in mice. Immunization with either Abg85b-AM or PA-AM conjugates elicited an AM-specific antibody response in mice. AM binding antibodies stimulated transcriptional changes in Mtb. Sera from AM conjugate immunized mice reacted against a broad spectrum of AM structural variants and specifically recognized arabinan fragments. Conjugate vaccine immunized mice infected with Mtb had lower bacterial numbers in lungs and spleen, and lived longer than control mice. These findings provide additional evidence that humoral immunity can contribute to protection against Mtb.